Identification and selection of wild Saccharomyces cerevisiae for improvement of Pisco from Quebranta grapes - Almanza Cano, Aybel (2023)
El Pisco stands as Peru's distilled spirit, crafted from recently fermented musts derived from native grape varieties known as "pisqueras". Yeasts serve as decisive microorganisms in the fermentation process, and the utilization of selected native strains confers competitive advantages for product typicity, standardization, and microbiological control within the production process. The aim was to identify and select native yeast strains for Quebranta grape Pisco production, isolated from Pisco production processes in the Ica Valley. Microbiological and molecular techniques were employed, utilizing ITS1-5.8S-ITS2 PCR-RFLP analysis for taxonomic identification. The assessment of yeast strains for Pisco production involved the physicochemical and organoleptic analysis of the distilled product obtained using the selected strains. Three isolates were evaluated for Pisco production, identified as Saccharomyces cerevisiae: UNA SC – 25, UNA SC – 49, and UNA SC – 54. Among these, the UNA SC-49 strain stood out due to displaying oenological characteristics distinct from the other strains. This work is the first documentation of native yeasts in Peru for musts derived from Quebranta grapes.